EDUCATIONAL MARKETING IN SCHOOL MANAGEMENT: AN ONTOLOGICAL, EPISTEMOLOGICAL, AND AXIOLOGICAL ANALYSIS FROM THE PHILOSOPHY OF SCIENCE PERSPECTIVE - Tarso Tarso; Asep Koswara; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2026)
This study aims to examine educational marketing in school management through the perspective of the philosophy of science, encompassing the dimensions of ontology, epistemology, and axiology. The study employed a qualitative approach with a library research design combined with philosophical-conceptual analysis. The research data were sourced from primary and secondary literature in the form of classic and recent books, articles from accredited and internationally reputable national journals, and policy documents relevant to educational marketing and school management. Data analysis was conducted through the stages of concept reduction, thematic categorization, philosophical interpretation, and argumentative synthesis. The results of the study indicate that ontologically, educational marketing is an integral part of the nature of school management as a public service institution oriented towards social and humanitarian missions. Epistemologically, educational marketing is built on the integration of theory, empirical data, and practical experience in school management, explained scientifically and reflectively. Meanwhile, axiologically, educational marketing demands the application of ethical values, honesty, social responsibility, and an orientation towards mutual education. The integration of these three dimensions emphasizes the importance of developing meaningful, ethical, and sustainable educational marketing.